Physical properties of the gamma-ray binary LS 5039 through low and high frequency radio observations - Marcote, Benito (2015)
LS 5039 is a gamma-ray binary displaying synchrotron emission at GHz radio frequencies with a small variability and without signatures of being orbitally modulated. A detailed study in the 0.15–15 GHz range has been carried out by analyzing VLA, GMRT and WSRT observations, obtaining an average spectrum and two quasi-simultaneous spectra. We have observed a persistent radio emission on day, week and year timescales, with a variability below 25% and with no signatures of orbital modulation at all frequencies except at 150 MHz, where the source remains undetected. The spectra reveal a power-law emission at high frequencies (& 1 GHz) and a turnover at about 0.5 GHz. We explain these spectra with a simple model of one-zone synchrotron emitting region. Synchrotron self-absorption and Razin effect explain the absorption at low frequencies (.1 GHz). With this model we have obtained an estimate of the physical properties of the radio emitting region of LS 5039, and derived a high mixing of the stellar wind within the relativistic plasma of the radio outflow.